(untitled) (Journal of Informatics Education and Research, 2025)
This study examines the role of Human Resource Management (HRM) practices in shaping faculty performance in Higher Education Institutions (HEIs) in Gujarat. Specifically, it explores the impact of career planning, training and development, performance appraisal, and reward and compensation on faculty performance. A quantitative research design was employed, collecting data from 288 faculty members across various HEIs. The data was analyzed using Exploratory Factor Analysis (EFA) and Structural Equation Modeling (SEM). The results reveal that all four HRM practices significantly influence faculty performance, with performance appraisal exhibiting the strongest effect. These findings underscore the necessity of strategic HRM interventions in HEIs to enhance faculty effectiveness and institutional success